Crisis en la frontera Colombo-Venezolana: derechos humanos, migraciones y conflicto geopolítico - Forero-Coronel, Jorge Alexander (2020)
The document presents an analysis of the crisis of the Colombian-Venezuelan border, in its three most notable expressions: i) the human rights crisis; ii) the migration crisis; iii) the geopolitical conflict. Based on the historical-geographical materialism, the analysis of the functionality of the border areas in the current world, to identify the general trends and characterize the particular variables that have determined the concretion of said crisis. The reflection is based on a documentary review, on the valuation of official figures of multilateral organizations, and on the presence in the field of the researcher as a political and academic agent. Controversial perspectives are raised around the substantive topics of the analysis and a critical view of the problem is advocated. Finally, a set of recommendations addressed to the National States, the multilateral organisms and the scientific communities are enunciated.